Efektivitas Pengelolaan Mutu Dosen Perguruan Tinggi Agama Islam Negeri - Muhammad Anggung Manumanoso Prasetyo; Husaini Husaini (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2021)
This research aims to describe and design integrated university governance model which is focused on lecturer quality control. This study reveals that high education shows no integrated governance. The research refers to evaluative study of High Education quality insurance concept. The research used survey approach with qualitative method. The informants in this research are leaders of High Education and lecturers. Results of the research show (1) quality control principles refer to organizational lifecycle concepts namely plan, do, act, check (PDAC); (2) implementation process refers to technical targets such as completeness of formal learning; (3) improvement of lecturer professionalism competence is conducted in the forms of education and training as well as comparative study; (4) monitoring activity on quality improvement evaluation is conducted by weekly routine meeting, mid-semester meeting and beginning of education year meeting. Results of the evaluation are used as the lecturer performance assessment and decision making instrument aspects. Implication of research results are manifested in the form of reward and punishment-based counseling. The research aims to examine the effects of quality control practices in state Islamic high education in Aceh